2020
DOI: 10.3390/w12030726
|View full text |Cite
|
Sign up to set email alerts
|

Combined Electrocoagulation and Chemical Coagulation in Treating Brewery Wastewater

Abstract: Significant over-strength discharge fees are often imposed on breweries for the disposal of high-strength effluent to sanitary sewers. In this research work, the removal performances of electrocoagulation (EC) compared with operating electrocoagulation and chemical coagulation in sequence (EC-CC) or vice-versa (CC-EC) was examined to determine the capability of treatment in reducing the strength of the wastewater. Optimal operating parameters regarding electrolysis time, initial pH, and applied power were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 23 publications
0
9
1
Order By: Relevance
“…Previous studies have shown that hybrid processes, such as combining EC with adsorption, can achieve removal efficiencies up to 20% higher than EC alone (Alfonso‐Muniozguren et al, 2021; Al‐Qodah et al, 2020). According to Swain et al (2020), Al‐Zghoul et al (2023), and Faraj et al (2024), these integrated processes can produce highly purified wastewater, enabling effective water reuse.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that hybrid processes, such as combining EC with adsorption, can achieve removal efficiencies up to 20% higher than EC alone (Alfonso‐Muniozguren et al, 2021; Al‐Qodah et al, 2020). According to Swain et al (2020), Al‐Zghoul et al (2023), and Faraj et al (2024), these integrated processes can produce highly purified wastewater, enabling effective water reuse.…”
Section: Introductionmentioning
confidence: 99%
“…At the light of this, to decontaminate the industrial effluents from heavy metal ions, the efforts integrate the different separation techniques such as chemical precipitation [19,20], membrane filtration [21,22], flocculation and chemical coagulation [23,24], biological treatment [25], ion exchange [26,27], photocatalytic degradation [28], advanced oxidation [29], nanofiltration [30][31][32], and adsorption [33][34][35][36][37][38]. However, the adsorption process remains the most interesting and attractive technique due to its simplicity, ease of handling, high efficiency, ability to remove a large amount of organic and inorganic pollutants, and availability [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Basically, a wastewater can be considered high strength when the major control parameters of this wastewater are in rather high concentrations such as of COD (Chemical Oxygen Demand), ammonia, suspended solids, or heavy metals, resulting sometimes in shock loadings. Wastewaters from the food industries mostly contain highly biodegradable organics in addition to increased nutrients (nitrogen and phosphorus) content [7][8][9]. Tannery is among the oldest industries in the world.…”
Section: Introductionmentioning
confidence: 99%
“…It involves the addition of certain chemicals (coagulant agents), such as alum or ferric salts, aiming to cause interactions between the colloids and the hydrolyzed Al 3+ or Fe 3+ cations and to form neutral or slightly positively charged micro-flocs. Recently, Swain et al (2020) [8] studied the combined chemical-and electro-coagulation process, used for the treatment of high-strength brewery wastewater, demonstrating the advantages of these treatment applications in terms of cost and high nutrient removal effectiveness. In addition, the coagulation-flocculation process has received greater attention, as it has been proven to be effective for the removal of various contaminants which may include toxic organic matter, heavy metals, viruses, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation